Improved constraints on sterile neutrino mixing from disappearance searches in the MINOS, MINOS+, Daya Bay, and Bugey-3 experiments - Adamson, P; An, FP; Anghel, I; Aurisano, A; Balantekin, AB; Band, HR; Barr, G; Bishai, M; Blake, A; Blyth, S; Cao, GF; Cao, J; et al. (American Physical Society, 2020)
Searches for electron antineutrino, muon neutrino, and muon antineutrino disappearance driven by sterile neutrino mixing have been carried out by the Daya Bay and MINOS+ collaborations. This Letter presents the combined results of these searches, along with exclusion results from the Bugey-3 reactor experiment, framed in a minimally extended four-neutrino scenario. Significantly improved constraints on the θ_{μe} mixing angle are derived that constitute the most constraining limits to date over five orders of magnitude in the mass-squared splitting Δm_{41}^{2}, excluding the 90% C.L. sterile-neutrino parameter space allowed by the LSND and MiniBooNE observations at 90% CL_{s} for Δm_{41}^{2}<13  eV^{2}. Furthermore, the LSND and MiniBooNE 99% C.L. allowed regions are excluded at 99% CL_{s} for Δm_{41}^{2}<1.6 eV^{2}.